2017
DOI: 10.1038/s41598-017-00869-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplasmonic Upconverting Nanoparticles as Orientation Sensors for Single Particle Microscopy

Abstract: We showed that the anisotropic disk shape of nanoplasmonic upconverting nanoparticles (NP-UCNPs) creates changes in fluorescence intensity during rotational motion. We determined the orientation by a three-fold change in fluorescence intensity. We further found that the luminescence intensity was strongly dependent on the particle orientation and on polarization of the excitation light. The luminescence intensity showed a three-fold difference between flat and on-edge orientations. The intensity also varied si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…Green et al . found that anisotropic shaped nanoplasmonic UCNPs, oriented with flat configuration, showed stronger emission intensity than those with edge orientation 32 . Calculations show that electric field strength is determined by the geometry of the UCNP.…”
Section: Resultsmentioning
confidence: 95%
“…Green et al . found that anisotropic shaped nanoplasmonic UCNPs, oriented with flat configuration, showed stronger emission intensity than those with edge orientation 32 . Calculations show that electric field strength is determined by the geometry of the UCNP.…”
Section: Resultsmentioning
confidence: 95%
“…Apart from their promising biomedical applications, the enlarged porous networks may facilitate the diffusion of volatile reactants to make the UC/chitosan aerogels useful as gas optical sensors. 48 …”
Section: Resultsmentioning
confidence: 99%
“…Larger particles, sizes >50 nm, are sufficiently bright to be imaged at the single particle level. [160] Sensitivity: UCMP-based thermal sensing have been demonstrated at high temporal (approximately ms) and thermal resolution (0.3-2.0 K) [42] and sensitivity (10 −5 % K −1 ) [146] with simple equipment requirements. Newer core-shell nanoparticles with higher luminescence efficiency, [41] are expected to enhance the sensitivity even further.…”
Section: Benchmarkingmentioning
confidence: 99%